A Systematic Review of the Concrete Durability Incorporating Recycled Glass - Mohammed A. Mansour, Mohammed A. Mansour; Ismail, Mohd Hanif; Qadir Bux alias Imran Latif, Qadir Bux alias Imran Latif; Abdullah Faisal Alshalif, Abdullah Faisal Alshalif; Abdalrhman Milad, Abdalrhman Milad; Walid Abdullah Al Barg, Walid Abdullah Al Barg (Mdpi, 2023)
This systematic literature review (SLR) aims to present and analyze the recent research on the effect of recycled glass (RG) on the durability of concrete applications in terms of transport properties, chemical attack, alkali-silica reaction (ASR), and freeze/thaw (FT). RG could be utilized in concrete as a replacement or addition in three forms, namely glass powder (GP), glass aggregate (GA), and glass fiber (GF). The methodology of this study was based on a criterion for the selection process of reviewed studies to assess and synthesize the knowledge of the durability of RG in concrete. The articles were assessed and screened, then 114 review articles were selected. The direction of utilization of RG in concrete depends on the type, particle size, and pozzolanic performance. The valorization of RG had a positive impact on the durability of concrete; however, the mutual synergy of multiple substitutions with glass also had better results. Nowadays, fine glass aggregate (FGA) could be promoted to be used as a partial substitute for sand due to the easiness of recycling. Furthermore, GF is strongly encouraged to be used in fiber concrete. An analytical framework that highlights the durability improvement of glass-modified concrete is presented. The results suggested that it is technically feasible to utilize glass as a part of concrete in the production of durable concrete. It provides a higher resistance to transport properties and chemical attacks by providing an extended lifespan. In addition, RG plays a great role in FT action in cold climates while it does not have a significant impact on ASR, provided refinement of glass results in the reduction of ASR and thus overcomes the expansion and cracks of concrete. However, up to 20% GP and up to 30% fine glass aggregate (FGA) could be replaced with cement and aggregate, respectively, to achieve a positive effect on durability based on the W/C ratio provided, not compromising the strength.